SYNTHESIS AND CHARACTERIZATION OF CHITOSAN-MAGNESIUM (II) COMPLEX IONS FROM SHRIMP SHELLS - BILAUT, IDALIA; Gauru, Imanuel; Wogo, Hermania Em; Lapailaka, Titus (Universitas Nusa Cendana, 2019)
Research has been carried out on the synthesis and characterization of Mg - Chitosan complex ions from shrimp shells using crosslink method. Chitosan isolation was made in four stages, namely deproteination, demineralization, depigmentation and deacetylation. The maximum degree of deacetylation (DD) of chitosan is 89%. Based on XRD and FTIR data, chitosan obtained is in the form of amorphous and there are typical wave number of chitosan, namely 3444.91 cm-1 and 1658.4 cm-1 associated to O-H, N-H dan C=O.